NF90 regulation of immune factor expression in response to malaria antigens - Idda, M. Laura (Cell Cycle, 2019)
Nuclear factor 90 (NF90) is a dual DNA- and RNA-binding protein expressed ubiquitously in mammalian cells, including monocytes. Here, to elucidate the function of NF90 in the immune response, we analyzed systematically its influence on gene expression programs in the human monocytic cell line THP-1 expressing normal or reduced NF90 levels. RNA sequencing analysis revealed many mRNAs showing differential abundance in NF90-silenced cells, many of them encoding proteins implicated in the response to immune stimuli and malaria infection. The transcription of some of them (e.g. TNF, LILRB1, and CCL2 mRNAs) was modulated by silencing NF90. Ribonucleoprotein immunoprecipitation (RIP) analysis further revealed that a subset of these mRNAs associated directly with NF90. To understand how NF90 influenced globally the immune response to malaria infection, lysates of red blood cells infected with Plasmodium falciparum (iRBC lysates) or uninfected/mock-infected (uRBC lysates) were used to treat THP-1 cells as a surrogate of malaria infection. NF90 affected the stability of a few target mRNAs, but influenced more generally the translation and secretion of the encoded cytokines after treatment with either uRBC or iRBC lysates. Taken together, these results indicate that NF90 contributes to repressing the immune response in cells responding to P. falciparum infection and suggest that NF90 can be a therapeutic target in malaria.